Microwave-Assisted Catalytic Method for a Green Synthesis of Amides Directly from Amines and Carboxylic Acids - Adam P. Zarecki; Jacek L. Kolanowski; Wojciech T. Markiewicz (Molecules, 2020)
Amide bonds are among the most interesting and abundant molecules of life and products of the chemical pharmaceutical industry. In this work, we describe a method of the direct synthesis of amides from carboxylic acids and amines under solvent-free conditions using minute quantities of ceric ammonium nitrate (CAN) as a catalyst. The reactions are carried out in an open microwave reactor and allow the corresponding amides to be obtained in a fast and effective manner when compared to other procedures of the direct synthesis of amides from acids and amines reported so far in the literature. The amide product isolation procedure is simple, environmentally friendly, and is performed with no need for chromatographic purification of secondary amides due to high yields. In this report, primary amines were used in most examples. However, the developed procedure seems to be applicable for secondary amines as well. The methodology produces a limited amount of wastes, and a catalyst can be easily separated. This highly efficient, robust, rapid, solvent-free, and additional reagent-free method provides a major advancement in the development of an ideal green protocol for amide bond formation.